The federal funds market over the 2007-09 crisis - Adam Copeland (Federal Reserve Bank of New York, 2019)
This paper measures how the 2007-09 financial crisis affected the U.S. federal funds market. I accomplish this by developing and estimating a structural model of this market, in which intermediation plays a crucial role and borrowing banks differ in their unobserved probability of default. The estimates imply that the expected probability of default increases 0.29 percentage point at the start of the crisis in mid-2007 and then gains a further 1.91 percentage points after the bankruptcy of Lehman Brothers. These increases do not cause a market freeze, however, because simultaneously there is a shift outward in the supply of funds. The model indicates that amid the turmoil of the crisis, lenders viewed the fed funds market as a relatively attractive place to invest cash overnight.
Keywords: D82; G01; G14; 330; asymmetric information; fed funds; intermediation; financial crisis